(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The advancement in adhesive dentistry is increased the success rate and the longevity of the prosthetic rehabilitation with their use. The present study is to evaluate the longevity of the missing teeth in the anterior region. MATERIAL & METHODS Two groups were made, one of them was single missing tooth and the other group was for 2 missing anterior teeth. Both groups were evaluated for the constant interval of 3 months up to 1 year. The all data was collected for the duration of the time and the data charts was prepared according to the data the statistical analysis done. RESULTS Kaplan Meier Survival Analysis for the statistical analysis was used to get the results. The p value obtained after the analysis for the single missing tooth was more significant than the double teeth. CONCLUSION Fibre reinforced composite fixed dental prosthesis (FRC FPD)for single tooth can be used as fixed conservative treatment as comparing to the two missing anterior teeth. The future is holding more of the variation. The study needs to be done for longer duration of time.